The Aspirin Tolerance Test in von Willebrand’s Disease - Barbui, Tiziano; Rodeghiero, Francesco; Dini, Enrico (Thrombosis and Haemostasis, 1977)
Opinions about the clinical value of aspirin tolerance test proposed by Quick in von Willebrand’s disease are conflicting.The results of the present study seem to support the view that a platelet defect, induced by aspirin, causes a significant lengthening of bleeding time only in the cases with severe von Willebrand factor deficiency.